THE EFFECT OF SHOPPING LIFESTYLE AND FASHION INVOLVEMENT ON IMPULSE BUYING BEHAVIOR: (Study on Retail Store Consumers at Delipark Mall Medan) - Ayu Askha Pratiwy; Onan Marakali Siregar (Transpublika Publisher, 2022)
Impulse buying is a buying decision by consumers spontaneously shortly after seeing a product offer, nowadays people are increasingly making impulse purchases because of their lifestyle, especially in fashion products. Retailers must understand the phenomenon and study the factors causing it so as to be able to maximize it, to be able to attract consumers to make impulse buying. This study aims to determine the effect of shopping lifestyle and fashion involvement on impulse buying behavior. The form of this research is quantitative research with an associative approach. The population in this study were consumers of Delipark Mall Medan with a sample of 100 people. The data collection technique was carried out with primary data with questionnaires through google form. The results of this study indicate that shopping lifestyle and fashion involvement have a significant effect on impulse buying behavior. In simultaneous testing, the shopping lifestyle and fashion involvement variables have a simultaneous effect on impulse buying behavior, with the magnitude of the relationship between the Shopping Lifestyle and Fashion Involvement variables on the Impulse Buying Behavior variable of 0.561, with a fairly close category. While the remaining 30% is influenced by other variables beyond this study.